Clinical profiles of patients undergoing permanent pacemaker implantation in a tertiary care hospital in India - Patra, Tusharkanti; Das, Asit (International Journal of Research in Medical Sciences, 2024)
Background: Despite an increase in the number of permanent pacemaker implantations in India over the last few decades, there are no systematic nationwide database recording the rate of implantation of permanent pacemaker, clinical conditions or types of pacemakers used for PPM implantation in India. Methods: A total of 5341 patients, admitted in the department of cardiology, Institute of Post Graduate Medical Education and Research, West Bengal, India from April, 2019 to August 2023 and received a permanent pacemaker were included in the study. Objective of the study was to provide information about the clinical profile and indications of patients receiving permanent pacemaker implantation (PPI). Results: Most (67%) of the recipients among the study population were males. The mean (± SD) age of patients in the present cohort was 63.59±11.82 years. The most frequent type of pacemaker used in this institution was VVIR (86.2%). The mean impedance for DDDR type pacemakers was 599.7±109.19 (range =416-1074) for ventricle and 915.9±116.2 (range =525-1240) for the atrium, while the threshold of DDDR type was 0.5±0.3 (range =0.1 -3) for ventricles and 0.3±0.2 (range =0.1-1.3) for the atrium. For VVIR type of pacemakers, the impedance for ventricles was 918.5±131.1 (range =120-1620), while the threshold for ventricle was 0.3±0.2 (range =0.1-2.2). The commonest indication of pacemakers were AV blocks (69%), of which the commonest was complete heart block (59.7%). Conclusions: In conclusion, male population were implanted with a higher number of pacemakers than females. No difference in age was noted among males and females in terms of the age of implantation. Use of single chamber VVIR types were higher than the dual chamber due to the pattern of government supply of pacemakers. Most common indication for pacemaker implantation was degenerative complete heart block.